Vibrational Properties and Charge Transfer in the Misfit-Layer Compound LaS-CrS2 - Kampmann, Felix; Panchakarla, Leela S.; Gillen, Roland; Tenne, Reshef; Maultzsch, Janina (Journal of Physical Chemistry C, 2021)
We present density functional theory calculations of the vibrational and electronic properties of the misfit-layer compound (MLC) LaS-CrS2 and its isolated sublayers to identify the vibrational modes of the compound. From the comparison of two model systems, (i) the fully relaxed misfit-layer compound supercell and (ii) its sublayers as isolated systems, we extract the charges, which are transferred between the two sublayers and the concomitant changes of the structural parameters upon formation of the supercell. The deformation within each sublayer indicates a strong influence of the charge transfer, confirming the important role of the interlayer interaction between the two sublayers. By comparing the vibrational properties of the two model systems, we assign several frequency regimes within the vibrations of the supercell to phonon branches of the sublayers. From polarized Raman spectra, we find that some of the Raman modes are directly inherited from the -point phonons of the hypothetical isolated 1T-CrS2 layer; other Raman modes are backfolded from the A1g-associated phonon branch of the 1T-CrS2 onto the misfit-layer compound MLC -point, which is a direct consequence of the supercell formation in LaS-CrS2.
CRIS-Team Scopus Importer:2021-05-14